Effects of a Smoke-Free Policy in Xi'an, China: Impact on Hospital Admissions for Acute Ischemic Heart Disease and Stroke - Chu, Meng; Liu, Zhiyan; Fang, Xinzhu; Wu, Yajun; Liu, Huannan; Zhao, Xuan; Zhang, Tianxiao; Wu, Qian; Tan, Fang (Frontiers in Public Health, 2022)
Background: Smoking and secondhand smoke (SHS) exposure rates are much higher in China than in other countries. A smoke-free policy was implemented on November 1, 2018, in Xi’an city, Shaanxi Province, China. This study aimed to evaluate the effect of the smoke-free policy in Xi’an city on changes of hospital admissions with in acute ischemic heart disease (AIHD) and stroke before and after policy implementation. Methods: All subjects were hospitalized for AIHD or stroke from February 9, 2017 to December 25, 2019 (150 weeks) in six randomly selected public hospitals in 36 tertiary hospitals Xi'an. The interrupted time series design and the generalized additive model (GAM) was used to compare immediate and annual percent changes in hospital admissions before and after policy implementation. Results: The study contained 31,400 cases (16,656 cases of AIHD and 14,744 cases of stroke) from 6 hospitals in Xi'an. Immediately after implementation of the smoke-free policy, admissions for AIHD were reduced significantly (-31.66%, 95% CI: - 39.45% to -22.86%), but admissions for stroke were not (-4.94%, 95% CI: -13.26% to 4.17%). The annual reduction in stroke-related admissions was significant (-14.54%, 95% CI: -23.53% to -4.49%), while the annual change in AIHD-related admissions increased significantly by 40.58% (95% CI: 22.08% to 61.87%). Although there was no significant reduction in AIHD admissions, stroke admissions were significantly reduced by -15.73% (from 7,350 to 6,194) after implementation of the smoke-free policy in Xi’an. Conclusion: The smoke-free policy in Xi’an has had different effects on AIHD and stroke hospital admissions. Xi'an should strengthen its smoke-free legislation and expand the implementation measures to maintain or achieve additional significant health benefits. These findings can also guide the formulation and implementation of regional and national smoke-free policies.